Analysis of modern atmospheric electrostatic field measuring instruments and methods - Povschenko, Oleksandr; Bazhenov, Viktor (Technology audit and production reserves, 2023)
The object of research is the process of measuring the strength of the atmospheric electrostatic field. This paper is devoted to an analytical review and comparative analysis of modern methods and instruments for measuring atmospheric electrostatic field strength. The results of scientific research and modern practical technologies, which are used to develop technical means and increase the accuracy of measuring the strength of electrostatic fields, are considered. In the work, the general functional requirements for the hardware of systems for measuring the atmospheric electrostatic field strength are formed and the main directions of research and practical tasks for its creation are defined. The design features and characteristics of existing measuring instruments are considered in detail. The advantages and disadvantages of electrometers, electrostatic field mills, microelectromechanical electrostatic field mills, and electric field imaging systems are determined given their portability, sensitivity, measuring frequency, accuracy, measurement range, linearity, and cost. The analysis of the state of modern methods and measuring instruments for the strength of the electrostatic field showed that one of the best solutions for measuring the electrostatic field strength of the atmosphere today is the use of an improved electrostatic field mill. It was determined that one of the important problems for ensuring the development of methods and means of atmospheric electrostatic field strength measuring is the need to generalize the structure of the measuring instruments and calculate its metrological characteristics. It has been established that solving the problem of increasing the accuracy of atmospheric electrostatic field strength measurement requires a comprehensive approach based on improving the design of the sensor structure of the meter, increasing the accuracy of navigation and positioning, increasing the autonomy of work, improving communication and data transmission systems, as well as ensuring high stability and reliability of work under the influence of external factors. Improving the structure and improving the characteristics of electrostatic field mills in the future will ensure the necessary accuracy, compactness, and availability for measurement and its inclusion in the automated system of atmospheric electrostatic field monitoring and forecasting.